Intrinsic immunogenicity of liposomes for tuberculosis vaccines: Effect of cationic lipid and cholesterol - Szachniewicz, M.M.; Neustrup, M.A.; van Meijgaarden, K.E.; Jiskoot, W.; Bouwstra, J.A.; Haks, M.C.; Geluk, A.; Ottenhoff, T.H.M. (European journal of pharmaceutical sciences, 2024)
Tuberculosis (TB) is still among the deadliest infectious diseases, hence there is a pressing need for more effective TB vaccines. Cationic liposome subunit vaccines are excellent vaccine candidates offering effective protection with a better safety profile than live vaccines. In this study, we aim to explore intrinsic adjuvant properties of cationic liposomes to maximize immune activation while minimizing aspecific cytotoxicity. To achieve this, we developed a rational strategy to select liposomal formulation compositions and assessed their physicochemical and immunological properties in vitro models using human monocyte-derived dendritic cells (MDDCs). A broad selection of commercially available cationic compounds was tested to prepare liposomes containing Ag85B-ESAT6-Rv2034 (AER) fusion protein antigen. 1,2-Dioleoyl-sn‑glycero-3-ethylphosphocholine (EPC)-based liposomes exhibited the most advantageous activation profile in MDDCs as assessed by cell surface activation markers, cellular uptake, antigen-specific T-cell activation, cytokine production, and cellular viability. The addition of cholesterol to 20 mol% improved the performance of the tested formulations compared to those without it; however, when its concentration was doubled there was no further benefit, resulting in reduced cell viability. This study provides new insights into the role of cationic lipids and cholesterol in liposomal subunit vaccines. [Display omitted]